Development Of Ultrasonic-Assisted Methyl Ester Process From Palm Oil Using Alkaline Earth Metal Oxide Catalysts - Mootabadi, Hamed (2010)
Biodiesel is an eco-friendly and alternative energy source for diesel engines that can be synthesized by transesterification of vegetable oil or animal fat with alcohols. Ultrasonic-assisted transesterification of palm oil in the presence of alkaline earth metal oxide catalysts (CaO, SrO and BaO) was investigated. The catalysts were characterized by SEM, surface analysis, AAS analysis and the Hammett indicator method. Batch transesterification process assisted by 20 kHz ultrasonic cavitation, with a maximum power of 200 W, was carried out to study the effects of reaction time (10–60 min), alcohol to palm oil molar ratio (3:1–15:1), catalysts loading (0.5–3 %) and variation of ultrasonic amplitudes (25-100 %). The activities of the catalysts were mainly related to their basic strength. The catalytic activity was in the sequence of CaO < SrO < BaO. Also, the yields achieved under ultrasonic increased from 5.5 % to 77.3 % (CaO), 48.2 % to 95.2 % (SrO), and 67.3 % to 95.2 (BaO) , respectively within a period of 60 minutes. Reuse of the catalysts after several successive cycles was also investigated. Significant reduction in catalytic activity was experienced by BaO catalyst while moderate decrease in the yield occurred for SrO and CaO catalysts. SrO supported over alumina was selected for the transesterification reaction. The optimum synthesis condition was achieved at 500 °C of calcinations temperature with 35 %wt of metal loading. Ultrasonic